A Self-Adaptive Chaos Particle Swarm Optimization Algorithm - Yalin Wu; Shuiping Zhang (Universitas Ahmad Dahlan, 2015)
As a new evolutionary algorithm, particle swarm optimization (PSO) achieves integrated evolution through the information between the individuals. All the particles have the ability to adjust their own speed and remember the optimal positions they have experienced. This algorithm has solved many practical engineering problems and achieved better optimization effect. However, PSO can easily get trapped in local extremum, making it fail to get the global optimal solution and reducing its convergence speed. To settle these deficiencies, this paper has proposed an adaptive chaos particle swarm optimization (ACPSO) based on the idea of chaos optimization after analyzing the basic principles of PSO. This algorithm can improve the population diversity and the ergodicity of particle search through the property of chaos; adjust the inertia weight according to the premature convergence of the population and the individual fitness; consider the global optimization and local optimization; effectively avoid premature convergence and improve algorithm efficiency. The experimental simulation has verified its effectiveness and superiority.